Pemanfaatan Daun Belimbing Wuluh (Averrhoa bilimbi L) dalam Bentuk Infusa dan Sediaan Celup terhadap Penurunan Berat Badan - Inaratul Rizkhy Hanifah; Suhartinah Suhartinah; Opstaria Saptarini (Fakultas Farmasi Universitas Setia Budi, 2014)
Obesity is excess weight due to the accumulation of fat cells. The adverse effects of obesity are high chances for the spread of degenerative diseases and in terms of aesthetic body look unattractive. This research was aimed to use bilimbi leaves as weight loss with varying doses in two dosage forms, namely infusion and tea bag. The test animals used were female white rats were grouped into: negative control group were given 0.5% CMC; positive control group were given xenicalÂ® a dose of 2.16 mg / 200 g BB rats; and a test group with a dose preparations bilimbi 5.0 mg/200 g BW, 10 mg/200 g BW, and 20 mg/200 g BW. The treatment were given for 30 days and observed weight. At the end of the treatment, animals dissected after anesthetized. Fats contained around abdominal weighed and the results recorded and compared. Results this study were the bilimbi leaves that has been made in the form of infusions and steeping tea bags in which both had effect as a weight loss in female rats wistar strain.